2000
DOI: 10.1016/s0022-5223(00)70176-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic off-pump coronary artery revascularization in multivessel disease: Experience of three hundred cases

Abstract: In a majority of patients, off-pump complete coronary artery revascularization is an acceptable alternative to conventional operations, yielding good results given progressive experience, rigorous technique, and adequate coronary artery stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(74 citation statements)
references
References 18 publications
5
65
1
3
Order By: Relevance
“…Importantly there data suggest that an off-pump strategy reduces the likelihood of reoperation for bleeding. There conclusion agrees with others [22,23] who have documented less perioperative bloodloss with off-pump CABG. The need for transfusion was significantly less in the beating heart group.…”
Section: Medline Embase Cochrane Controlled Trialssupporting
confidence: 93%
“…Importantly there data suggest that an off-pump strategy reduces the likelihood of reoperation for bleeding. There conclusion agrees with others [22,23] who have documented less perioperative bloodloss with off-pump CABG. The need for transfusion was significantly less in the beating heart group.…”
Section: Medline Embase Cochrane Controlled Trialssupporting
confidence: 93%
“…In our study, we observed lower rates of hemorrhagic shock and also decrease in the need for blood transfusions in the OPCAB group compared to on-pump CABG group. This removal of blood transfusion reduces the risk of infections [13]. In our study, women undergoing OPCAB had less pneumonia and sepsis compared to patients undergoing on-pump CABG, however, we can not say that this decrease was necessarily due to decrease in blood product transfusions, since we have not performed that analysis.…”
Section: Discussioncontrasting
confidence: 54%
“…Observational studies have already suggested similar results to conventional CABG [15]. The effectiveness of off-pump CABG surgery has been demonstrated in patients with multivessel disease [22], or in those with disease in the left coronary artery [16], and in high-risk patients preoperatively as well [17].…”
Section: Discussionmentioning
confidence: 87%